Empathy: a discursive psychological exploration of the construct within the context of the therapeutic relationship - Walker, Tammy L. (2011)
Introduction: Empathy is considered to be an important therapist offered condition. Historically the exploration of empathy has employed quantitative methodologies. It is argued that these methodologies cannot capture the socially constructed nature of psychological concepts and instead regard empathy as problematic due to its inconsistently applied definition.